Environmental governance in Latin America: Towards an integrative research agenda - Baud, Michiel; de Castro, Fabio; Hogenboom, Barbara (European Review of Latin American and Caribbean Studies, 2011)
Latin America plays an important international role with regard to environmental governance. Knowledge generated by empirical and theoretical studies on environmental challenges can support the renewed efforts to achieve equitable and sustainable natural resource use in the region. Although linkages between social and environmental dimensions have been academically explored since the 1990s, new trends in environmental governance in Latin America deserve a comprehensive analytical approach. This Exploration presents relevant emerging research topics and provides a brief overview of relevant elements and ‘cross-overs’ for an integrative analysis. The authors argue that in order to enhance ‘Latin American perspectives’ to solving socioenvironmental dilemmas, several research streams need to be brought together in integrative frameworks that can address complex questions related to interactions between state, civil society and market actors at multiple scales. With a consortium of ten Latin American and European institutions, they aim to contribute to the development of such frameworks through the project Environmental Governance in Latin America and the Caribbean: Developing Frameworks for Sustainable and Equitable Natural Resource Use (ENGOV).Resumen: Gobernanza ambiental en América Latina: Hacia un programa integrado de investigaciónAmérica Latina juega un importante papel internacional en el ámbito de la gobernanza ambiental. El conocimiento generado por estudios teóricos y empíricos sobre retos ambientales puede sostener renovados esfuerzos por llegar a un uso equitativo y sostenible de los recursos naturales en la región. Aunque las conexiones entre las dimensiones social y ambiental han sido estudiadas en la academia desde los años noventa, nuevas tendencias en gobernanza ambiental en América Latina merecen un enfoque analítico comprehensivo. Esta Exploración presenta nuevos y relevantes temas de investigación y ofrece una breve perspectiva de los elementos relevantes y ‘cross-overs’ para un análisis integrativo. Los autores plantean que para mejorar las “perspectivas latinoamericanas” para resolver dilemas socio-ambientales, se necesita reunir en marcos integradores varias tendencias de investigación que puedan tratar asuntos complejos relacionados con las interacciones entre el estado, la sociedad civil y el mercado en múltiples escalas. Con un consorcio de diez instituciones latinoamericanas y europeas, se espera contribuir al desarrollo de esos marcos interpretativos a través del proyecto Gobernanza Ambiental en América Latina y el Caribe: Hacia Marcos Analíticos para el Uso Equitativo y Sostenible de los Recursos Naturales (ENGOV).